The Risk and Associated Factors of Female Sexual Dysfunction (FSD) in Women with Psoriasis - J, Adawiyah; AAK, Moonyza; S, Hatta; AM, Mohd Rizal; BBY, Felix; NJ, Nik Ruzyanei; M, Marhani; D, Srijit; CG, Ng (IIUM Medical Journal Malaysia, 2017)
Introduction: Psoriasis is a chronic, immune mediated, hyperproliferative skin disease that has substantial impact on the sexual functions. This study aimed to determine the prevalence and associated factors of female sexual dysfunction (FSD) in patients with psoriasis. Methods: A cross-sectional study involving 79 women with psoriasis attending two Dermatology Outpatient Clinics were interviewed and assessed for female sexual dysfunction and severity of psoriasis. The socio-demographic and clinical characteristics of the subjects were compared between the women with and without sexual dysfunction. The subjects were interviewed using Mini International Neuropsychiatric Interview (M.I.N.I.) to exclude any existing psychiatric illness. Sexual dysfunction was assessed using a validated questionnaire on sexual function and the severity of psoriasis was assessed using Psoriasis Area and Severity Index (PASI). Results: The prevalence of FSD in the patients with psoriasis was 20.3%, with hypoactive sexual desire being the most prevalent problem (44.3%). Sexual dysfunction was associated with older age, menopause, low body mass index, longer duration of marriage and presence of psoriasis in the genital area. Female sexual dysfunction was highly prevalent in patients with psoriasis. Conclusion: Management of psoriasis should include assessment in patients’ sexual health. Genital area involvement with psoriasis should not be overlooked as it can cause significant psychosexual distress.